Regulation of Blood Pressure, Appetite, and Glucose by Leptin After Inactivation of Insulin Receptor Substrate 2 Signaling in the Entire Brain or in Proopiomelanocortin Neurons. Issue 2 (February 2016) - do Carmo, Jussara M.; da Silva, Alexandre A.; Wang, Zhen; Freeman, Nathan J.; Alsheik, Ammar J.; Adi, Ahmad; Hall, John E.
Abstract : Insulin receptor substrate 2 (IRS2) is one of the 3 major leptin receptor signaling pathways, but its role in mediating the chronic effects of leptin on blood pressure, food intake, and glucose regulation is unclear. We tested whether genetic inactivation of IRS2 in the entire brain (IRS2/Nestin-cre mice) or specifically in proopiomelanocortin (POMC) neurons (IRS2/POMC-cre mice) attenuates the chronic cardiovascular, metabolic, and antidiabetic effects of leptin. Mice were instrumented with telemetry probes for measurement of blood pressure and heart rate and with venous catheters for intravenous infusions. After a 5-day control period, mice received leptin infusion (2 μg/kg per minute) for 7 days. Compared with control IRS2 flox/flox mice, IRS2/POMC-cre mice had similar body weight and food intake (33±1 versus 35±1 g and 3.6±0.5 versus 3.8±0.2 g per day) but higher mean arterial pressure (MAP) and heart rate (110±2 versus 102±2 mm Hg and 641±9 versus 616±5 bpm). IRS2/Nestin-cre mice were heavier (38±2 g), slightly hyperphagic (4.5±1.0 g per day), and had higher MAP and heart rate (108±2 mm Hg and 659±9 bpm) compared with control mice. Leptin infusion gradually increased MAP despite decreasing food intake by 31% in IRS2 flox/flox and in Nestin-cre control mice. In contrast, leptin infusion did not change MAP in IRS2/Nestin-cre or IRS2/POMC-cre mice. The anorexic and antidiabetic effects of leptin, however, were similar in all 3 groups. These results indicate that IRS2 signaling in the central nervous system, and particularly in POMC neurons, is essential for the chronic actions of leptin to raise MAP but not for its anorexic or antidiabetic effects. Abstract : Supplemental Digital Content is available in the text.